Higher regularity for the Signorini problem for the homogeneous, isotropic Lamé system. (April 2022) - Rüland, Angkana; Shi, Wenhui
Abstract: In this note we discuss the (higher) regularity properties of the Signorini problem for the homogeneous, isotropic Lamé system. Relying on an observation by Schumann (1989), we reduce the question of the solution's and the free boundary regularity for the homogeneous, isotropic Lamé system to the corresponding regularity properties of the obstacle problem for the half-Laplacian.